(untitled) (KULT_online, 2014)
Political art and theater have recently experienced significant blooming periods in the U.S. and U.K. In context of the so-called "War on Terror" artists – especially in the theater world – produced projects and performances that partly line up with internationally relevant theory-driven developments and partly draw from largely discredited models of political theater. Jenny Spencer’s Political and Protest Theatre after 9/11 – Patriotic Dissent brings together essays by key scholars and theorist-practitioners in the field, which offer the so far most comprehensive view on the decidedly significant moments in British and American theater history. Sara Brady’s Performance, Politics, and the War on Terror – "Whatever it Takes" explores the role of performance in the "War on Terror" in all its complexity, covering both the performance of politics and politicians as well as various approaches to and instances of political performance in the aesthetic realm.